Manfredo Tafuri, Fernando Aliata, Anahi Ballent, Alejandro Crispiani, Mercedes Daguerre, Adrián Gorelik, Jorge Francisco Liernur, Graciela Silvestri, Tafuri en Argentina, Santiago de Chile, ARQ ediciones, 2019, 274 páginas - Agüero, Ana Clarisa (2020)
Fil: Agüero, Ana Clarisa. Universidad Nacional de Córdoba; Argentina.